PENGARUH KOMPENSASI FINANSIAL DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN HOTEL THE PADE ACEH BESAR - Nurbismi Nurbismi; Zulfajri Zulfajri (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2021)
The purpose of study was to determine whether effect of financial compensation and work discipline on employee performance at The Pade Aceh Besar Hotel. In this study using kompesensi financially independent variable (X1) and discipline (X2).The analytical method used is multiple linear regression analysis. The sample used in this study were 71 respondents who were taken by total sampling all employees of The Pade Hotel. The data obtained is primary data which is the result of respondents' answers to the distributed questionnaires. The results of this study indicate that there is a simultaneous influence on the variables of financial compensation and work discipline on employee performance at The Pade Aceh Besar Hotel as evidenced by the acquisition of aF value of 31,857 > Ftable of 3.13. The results of this study also show that financial compensation and work discipline variables have a partially significant effect on performance decisions as evidenced by the acquisition of a t-value count of t-count of 7337 > 1.994. In the determination test there is an influence of 46% of the independent variable (financial compensation). and work discipline) on the dependent variable (employee performance). Meanwhile, as much as 54% is influenced by other variables and is not included in this regression analysis.